Some observations on meaningful and objective inference in radioecological field studies. Issue 7 (13th June 2022) - Jackson, Joseph A.; Antwis, Rachael E.; Beresford, Nicholas A.; Wood, Michael D.
Abstract: Anthropogenic releases of radiation are of ongoing importance for environmental protection, but the radiation doses at which natural systems begin to show effects are controversial. More certainty is required in this area to achieve optimal regulation for radioactive substances. We recently carried out a large survey (268 sampled animals and 20 sites) of the association between environmental radiation exposures and small mammal gut‐associated microbiomes (fungal and bacterial) in the Chornobyl Exclusion zone (CEZ). Using individual measurements of total absorbed dose rates and a study design and analyses that accounted for spatial non‐independence, we found no, or only limited, association. Watts et al. have criticised our study: for not filtering candidate non‐resident components prior to our fungal microbiome analyses, for our qualified speculations on the relative merits of faecal and gut samples, and for the design of our study which they felt lacked sufficient replication. The advantage of filtering non‐resident‐fungal taxa is not clear and it would not have changed the null (spatially adjusted) association we found between radioactive dose and mycobiome composition because the most discriminatory fungal taxa with regard to dose were non‐resident taxa. We maintain that it was legitimate for us to make qualified discussion comments on the differences in results between our faecal and gut microbiome analyses and on the relative merits of these sample types. Most importantly, the criticism of our study design by Watts et al. and the designs and analysis of their recent studies in the CEZ show a misunderstanding of the true nature of independent replication in field studies. Recognising the importance of spatial non‐independence is essential in the design and analysis of radioecological field surveys. Abstract : A habitat in the Red Forest, Chornobyl Exclusion Zone, Ukraine. The criticism of our study design (Antwis et al., 2021) by Watts et al. (2022), and the designs and analysis of their recent studies in the CEZ, show a misunderstanding of the true nature of independent replication in field studies. Recognizing the importance of spatial non‐independence is essential in the design and analysis of radioecological field surveys.